Encouraging efficacy of a comprehensive therapy consisting of sintilimab, bevacizumab biosimilar IBI305, hypo-fractionated intensity-modulated radiotherapy, and oxaliplatin for a maxillary metastasis from hepatocellular carcinoma: A case report and literature review - Liang, Xuexia; Liu, Qiaodan; Yao, Wei; Zhu, Shuqin (Frontiers in Oncology, 2022)
Oro-maxillo-facial metastasis from hepatocellular carcinoma (HCC) are very rare, and reports on treating maxillary metastasis from HCC are unavailable. Anti-angiogenesis therapy combined with immunotherapy represented by programmed cell death 1 (PD-1) or its ligand (PD-L1) inhibitors has become the standard treatment of advanced HCC. However, integrating chemoradiotherapy into immunotherapy-bevacizumab combination therapy has not been reported. Here we presented a female Chinese with maxillary metastasis from HCC who achieved a nearly complete response (CR) to a quadruple treatment scheme consisting of a PD-1 monoclonal antibody sintilimab, bevacizumab biosimilar IBI305, hypo-fractionated intensity-modulated radiotherapy (hfIMRT) and concurrent oxaliplatin. This comprehensive treatment is an innovative and effective therapy for advanced HCC.